Contributions towards smart cities : exploring block level census data for the characterization of change in Lisbon - Antunes, Jorge Manuel Alves (2016)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management